Satisfacción laboral y síndrome de burnout en profesionales del sector salud - Mellarez Aliaga, Joel Víctor (2024)
The aim of this applied review was to determine the relationship between burnout syndrome and job satisfaction among employees in both public and private healthcare sectors. To achieve this, a systematic PRISMA review (Page et al., 2021) was conducted using the EBSCOhost and ProQuest databases. Studies presenting significant statistics between job satisfaction and burnout syndrome were selected (n=11). A significant negative relationship between both variables was evidenced. Additionally, some factors that may reduce and prevent burnout syndrome among healthcare workers, such as social relationships and family support, were identified. Therefore, it is suggested that hospitals and healthcare centers develop workshops to promote teamwork and provide spaces for communication to enhance interaction between employees and hierarchical superiors. Furthermore, it is recommended that organizational leaders establish clear policies defining employee objectives and facilitating their achievement in the short and medium term, which could contribute to increasing employee job satisfaction.